Antibody-functionalized iron-based nanoplatform for ferroptosis-augmented targeted therapy of HER2-positive breast cancer - Jingchao Gao; Tong Ye; Hongkun Miao; Mingjiang Liu; Li Wen; Yi Tian; Zhiguang Fu; Li Sun; Lihong Wang; Yu Wang (Bioactive Materials, 2025)
Human epidermal growth factor receptor 2 positive (HER2+) breast cancer, as a subtype with high invasiveness and poor prognosis, faces issues of intertumoral heterogeneity and signaling pathway dysregulation leading to trastuzumab resistance in clinical treatment. Therefore, innovative therapeutic strategies are urgently needed to enhance treatment efficacy and improve patient prognosis. In this study, we proposed an antibody-targeted nanoplatform responsive to the tumor microenvironment, aiming to induce ferroptosis in HER2+ breast cancer cells and thereby enhance the sensitivity to HER2-targeted drugs. Fe-MOF@Erastin@Herceptin (FEH) was prepared by loading Erastin onto mesoporous Fe-MOF and modifying it with trastuzumab (a HER2+ breast cancer cell-specific antibody). This platform gradually releases trastuzumab, Erastin, and Fe3+ in the tumor microenvironment. The modification of trastuzumab enhances tumor cell targeting while reducing toxicity to non-target cells and tissues. Erastin inhibits system XC− to reduce glutathione (GSH) synthesis. Fe3+ consumes glutathione and reduces itself to Fe2+ via a reduction reaction, which further enhances the catalytic effect of H2O2 and triggers the Fenton reaction to generate large amounts of reactive oxygen species (ROS). In the antibody-targeted cascade reaction, decreased intracellular GSH content and increased Fe2+ and ROS can further promote lipid peroxidation and down-regulation of glutathione peroxidase 4 (GPX4) in breast cancer cells, inducing ferroptosis. The experimental results indicate that FEH can significantly improve the tumor microenvironment by enhancing ferroptosis effects, providing a potential new strategy for precision therapy of HER2+ breast cancer cells.